Genome-wide analysis of genomic alterations induced by oxidative DNA damage in yeast - Zhang, Ke (Nucleic Acids Res, 2019)
Oxidative DNA damage is a threat to genome stability. Using a genetic system in yeast that allows detection of mitotic recombination, we found that the frequency of crossovers is greatly elevated when cells are treated with hydrogen peroxide (H(2)O(2)). Using a combination of microarray analysis and genomic sequencing, we mapped the breakpoints of mitotic recombination events and other chromosome rearrangements at a resolution of about 1 kb. Gene conversions and crossovers were the two most common types of events, but we also observed deletions, duplications, and chromosome aneuploidy. In addition, H(2)O(2)-treated cells had elevated rates of point mutations (particularly A to T/T to A and C to G/G to C transversions) and small insertions/deletions (in/dels). In cells that underwent multiple rounds of H(2)O(2) treatments, we identified a genetic alteration that resulted in improved H(2)O(2) tolerance by amplification of the CTT1 gene that encodes cytosolic catalase T. Lastly, we showed that cells grown in the absence of oxygen have reduced levels of recombination. This study provided multiple novel insights into how oxidative stress affects genomic instability and phenotypic evolution in aerobic cells.